Dartmouth-Hitchcock Medical Center: Spine Care - Huckman, Robert S.; Huckman, Robert S.; Porter, Michael E.; Gordon, Rachel; Kindred, Natalie; Weinstein, James (2009)
Describes the Spine Center at Dartmouth-Hitchcock Medical Center, a multidisciplinary unit that offers patients suffering from spinal problems 'one-stop' access to a range of providers including orthopedic surgeons, neurosurgeons, neurologists, medical specialists in physical medicine and pain management, mental health providers, and occupational and physical therapists. The Center was created to address what its founder, James Weinstein, M.D., saw as the uncoordinated and inefficient delivery of spinal care in the United States. The Center emphasized using non-surgical treatments (e.g., physical therapy and exercise, behavioral modification, pain-relieving drugs) as either a complement to, or substitute for, surgical procedures, and patients were actively engaged in the process of determining what type of care to pursue. In addition, Weinstein and his staff collected data from the Center's clinical practice to conduct academic research on the outcomes and cost-effectiveness of various approaches to treatment. The case allows for a critical analysis of the Spine Center's unique approach to care delivery and provides an opportunity to examine the applicability of this model in other clinical areas.